Over a century of pear breeding at the USDA - Gottschalk, Christopher; Bell, Richard L.; Volk, Gayle M.; Dardick, Chris (Frontiers in Plant Science, 2024)
The U.S. Department of Agriculture (USDA) has performed European pear (Pyrus communis L.) scion breeding for over a century. The breeding program started in the early 1900s by Merton B. Waite in the Washington D.C. area and the program's main goal was to develop host resistance to the devastating disease fire blight, caused by Erwinia amylovora.Most of the historic European pear cultivars being produced in the U.S. were susceptible to fire blight, prompting a need to breed for resistance. More than six generations of USDA breeders have continued this effort to breed disease-resistant European pears. Along with fire blight resistance, the pear breeding programs sought improved fruit quality, cold hardiness, and resistance to psylla (Cacopsylla pyricola Foërster), a significant insect pest of pear. Herein, we discuss the history of the program through each generation of breeder(s). We also present breeding aims, parental selection, and releases. In total, the program has released ten named pear varieties between 1938 and 2022. Funding Source: USDA ARS in-house project number 8080-21000-033-000-D. USDA is an equal opportunity provider and employer.